РАЗВИТИЕ ЛАДОВОЙ ТЕОРИИ АЗЕРБАЙДЖАНСКОЙ МУЗЫКИ В ХХ-ХХI вв. - Шихалиев Имран Нагдали (International Journal of Innovative Technologies in Social Science, 2019)
Uzeyir Hajibeyov is the founder of Azerbaijani professional music and national musicology. “Principles of Azerbaijani Folk Music” U. Hajibeyov is the first fundamental theoretical work on Azerbaijani music. There are seven main and three auxiliary ways in Azerbaijani music. Azerbaijani modes are formed when tetrachords are connected. There are five types of tetrachord and four ways to connect. Azerbaijani modes are built on the basis of mugams of the same name. Each stage of the modes from which mode is formed has a specific function. Alterations in Azerbaijani frets arise for several reasons.